Zanjan , Name and Origin: A Glimpse of Its History (Journal of the College of Education for Women, 2019)
The aim of study is to shed light on an Islamic city which is unknown for a lot of people, it can have an old history in Parisian country and many events happen with it , This city is characterized with political, military, economic scientific ,and social features, This city is called Zanjan and it is one of the most important cities because it dates back to the period of post history and it has a good geographic location whereas it was, passage for trade caravans to pass through as well its land which was specialized in agriculture and industry. the study follows chronological order of historical events for the city, one of the most significant conclusions is to think that this city does belong to artifacts and it is an old city and it has an old history,this city was founded by the king Ardsheer Babkan and he was a big Sasanian king, a lot of different religions like old Parisian zaradishat, Christianity, and Jewish. The study tries to uncover nature of developments and political events which the city witnessed where it was front for different political powers in order to take control over Abbasid succession, As for geographical location, it can have big impact on different dimensions .